Simulations of Asymmetric Membranes Illustrate Cooperative Leaflet Coupling and Lipid Adaptability - Blumer, Madison; Harris, Sophia; Li, Mengzhe; Martinez, Luis; Untereiner, Michael; Saeta, Peter N.; Carpenter, Timothy S.; Ingólfsson, Helgi I.; Bennett, W. F. Drew (Frontiers in Cell and Developmental Biology, 2020)
Biological membranes are composed of lipid bilayers that are often asymmetric with regards to the lipid composition and/or aqueous solvent they separate. Studying lipid asymmetry both experimentally and computationally is challenging. Molecular dynamics simulations of lipid bilayers with asymmetry are difficult due to finite system sizes and time scales accessible to simulations. Due to the very slow flip-flop rate for phospholipids, one must first choose how many lipids are on each side of the bilayer, but the resulting bilayer may be unstable (or metastable) due to differing tensile and compressive forces between leaflets. Here we use a large number of bilayer simulations to investigate a number of different asymmetric membrane systems, both with atomistic and coarse-grained models. Asymmetries studied include differences in number of lipids, lipid composition (unsaturated and saturated tails and different headgroup), and chemical gradients between the aqueous phases. We also address how cholesterol (which flip-flops relatively quickly) influences membrane asymmetries. Our results show how each leaflet is influenced by the other and can mitigate the structural changes to the bilayer structure. Cholesterol can respond to changes in bilayer asymmetry to alleviate some of the effect on the bilayer structure, but that will alter its leaflet distribution and its chemical potential varies with leaflet composition. Our results highlight the importance of membrane asymmetry on bilayer properties, the influence of lipid headgroups, tails and cholesterol on asymmetry, and the ability of lipids to adapt to different environments.